The Implementation of Learning Community Culture as a Strategy to Accelerate Differentiated Deep Learning - Setyawati Setyawati (Journal of Education and Teaching Learning, 2026)
This study examined how Learning Community (Komunitas Belajar/KomBel) culture at SMAN 1 Bagan Sinembah contributed to accelerating differentiated deep learning. The study was motivated by the PLC Lite phenomenon, in which learning community activities were conducted formally but had not yet produced meaningful professional collaboration among teachers. A qualitative approach with a single embedded case study design was employed. Data were collected through participatory observation, semi-structured in-depth interviews, and document analysis involving teachers, the KomBel coordinator, and the principal selected purposively. Data were analyzed using Miles, Huberman, and Saldana's interactive thematic model. The findings show that KomBel functions as a trust-based professional learning ecosystem through reflective collaboration, student data utilization, and co-creation of differentiated teaching materials. Differentiated instruction produced multidimensional effects on students, especially affective gains such as self-confidence and intrinsic motivation before cognitive improvement. The sustainability of KomBel requires both systemic institutional support and an authentic collaborative culture.